Development and application of mathematical models in gait characterisation after stroke - Tan, Ming Gui (2019)
The number of stroke has increased every years according to American Heart Association (AHA), World Health Organization (WHO) and National Stroke Association of Malaysia (NASAM). These numbers have raised concerns among medical and rehabilitation professionals who manage this neurological disorder. For this project, we aim to develop a sophisticated gait analysis system to help the recovery of stroke patients. This proposed gait analysis system can help clinicians to assess the gait pattern and plan a suitable rehabilitation treatment for stroke patients systematically. It started with the development of gait sensor system. In this study, we are interested to study about the kinematics and kinesiology parameters of stroke patients. Therefore, we developed a low-cost inertial based sensor system and employed commercial ShimmerSensing sEMG sensors. A 3D high-speed camera was used to validate the inertial based sensor system. The parameters obtained from the sensor system were further analysed to extract valuable features for gait characterisation and gait classification.